Characteristics of non-magnetic nanoparticles in magnetically fluidized bed by adding coarse magnets - Zhou, Li; Diao, Run-li; Zhou, Tao; Kage, Hiroyuki; Mawatari, Yoshihide (Journal of Central South University, 2011)
The fluidization behavior of SiO 2 , ZnO and TiO 2 non-magnetic nanoparticles was investigated in a magnetically fluidized bed (MFB) by adding coarse magnets. The effects of both the amount of coarse magnets and the magnetic field intensity on the fluidization quality of these nanoparticles were investigated. The results show that the coarse magnets added to the bed lead to a reduction in the size of the aggregates formed naturally by the primary nanoparticles. As the macroscopic performances of improved fluidization quality, the bed expansion ratio increases whilst the minimum fluidization velocity decreases with increasing the magnetic field intensity, but for TiO 2 nanoparticles there exists a suitable magnetic field intensity of 0.059 6 T. The optimal amounts of coarse magnets for SiO 2 , ZnO and TiO 2 non-magnetic nanoparticles are 40%, 50% and 60% (mass fraction), respectively. The bed expansion results analyzed by the Richardson-Zaki scaling law show that the exponents depend on both the amount of coarse magnets and the magnetic field intensity.